Amphibian Diversity in altitude 1440 meters above sea level in the district Kebayakan of Central Aceh - Muzakiruddin Muzakiruddin; Abdullah Abdullah; Dahlian Oesman (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
Amphibians are one of the components of the ecosystem which has a very important role, both ecologically and economically. Research on amphibians in Indonesia is still very limited. Forest communities to change the area into other uses. This study aims to: (1) Knowing what types of amphibians found at an altitude of 1440 meters above sea level. (2) Determine the level of amphibian diversity in every altitude 1440 meters above sea level. This research was conducted in the District Kebayakan Central Aceh. The method used in obtaining data amphibian is Visual Encounter Survey by purposive sampling at different heights, with sampling using line transect along 500 meters. Analysis of descriptive data. The physical characteristics of the study sites showed a corresponding value to the lives of amphibians in general. The water temperature ranges from 18 to 20 ° C and air temperatures ranging from 18 ° to 24 ° C while the relative humidity ranges from 37% to 44% with a pH of 7 is relatively neutral and the salinity of the water is worth 0. The conclusion of research is the diversity of amphibians found in the District Kebayakan Central Aceh moderate.